2023
DOI: 10.2514/1.j062572
|View full text |Cite
|
Sign up to set email alerts
|

Toward More General Turbulence Models via Multicase Computational-Fluid-Dynamics-Driven Training

Abstract: The accuracy of machine-learned turbulence models often diminishes when applied to flow cases outside the training data set. In an effort to improve the predictive accuracy of data-driven models for an expanded set of cases, an extension of a computational fluid dynamics (CFD)-driven training framework consisting of three key steps is proposed. Firstly, a list of candidate flow-related parameters is selected to supplement Pope’s general tensor basis hypothesis. Secondly, modeling an additional production term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The resultant turbulent time and length scales are then used to calculate the target non-dimensional second-moment and the flow features by Eq. ( 7)− (9). Finally, around two millions data points for all the quantities are sampled over the whole domain with refinement in the inlet jet penetration region.…”
Section: Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant turbulent time and length scales are then used to calculate the target non-dimensional second-moment and the flow features by Eq. ( 7)− (9). Finally, around two millions data points for all the quantities are sampled over the whole domain with refinement in the inlet jet penetration region.…”
Section: Data Preparationmentioning
confidence: 99%
“…Researchers developed machine learnt scalar flux models for flows with different Prandtl numbers [5], different Reynolds numbers [32] in a channel, and for various Rayleigh numbers in natural, forced and mixed convection [39,40]. At the same time, several studies have also tried to explore physicsconstrained data-driven modelling via feature-space engineering [33], interpretable tree-based modelling [12], and by attempting to increase the generalizability of the models through multi-case CFD-driven training [9]. Amongst the different training approaches, the symbolic regression has the advantage of generating interpretable closed-form mathematical models, which are easier to implement and interpret.…”
Section: Introductionmentioning
confidence: 99%
“…As a solution to this issue, Fang et al [139] suggested including more cases in the training process of CFD-driven optimisation which means that in each evaluation of the optimisation algorithm, more CFD simulations have to be completed to include more a posteriori results in the training process. Fang et al [139] investigated this solution with a multi-case CFD-driven optimisation including different turbulent phenomena. They reported that this solution helped with the generalisability of the new model, however, their new models still have to be separated into either wall-free or wall-bounded flows.…”
Section: Turbulence Modelling For Separated Flowsmentioning
confidence: 99%
“…One of the most important topics in data-driven RANS modelling is the generalisability of the new models for unseen cases [138]. It has been suggested that using a multi-case CFDdriven approach to consider different turbulent phenomena during the optimisation process can help with the generalisability of the new model [139]. However, even these new models are still specific to either wall-free or wall-bounded flows; therefore, the generalisability problem requires further investigation.…”
Section: Vi1 Introductionmentioning
confidence: 99%